PERSEPSI MASYARAKAT TERHADAP EKSPLOITASI PANAS BUMI DI WILAYAH KERJA PERTAMBANGAN KALDERA RAWA DANAU - Uga Halia Dinan; Nurul Hidayati (Jurnal Kommunity Online, 2021)
The presence of a PLTP factory construction project or geothermal power plant in Padarinicang District, Serang Regency has created a pro attitude among public officials and the community around the factory location and road opening. This research was carried out by using mix methods. Mix methods is a step of research that combines two forms of approach; wuantitative and qualitative research. The study of the sosial conditions of the community was carried out by collecting questionnaire data and in-depth interviews. The results of the study indicate that the community's perception and understanding of this development is the low incidence of conflicts and conflicts in the community, deep sosialization and sustainable solutions are the most effective for solving this problem.